Dataset: Digital Forensic Literature with a Focus on Software: Trends, Institutions, and Authors (2012-2022) - Pandu Sarigati Sari; Mochammad Tanzil Multazam (Proceedings of The ICECRS, 2022)
This data article presents a thorough examination of digital forensic literature with a focus on software from 2012 to 2022, retrieved from lens.org, with the aim of identifying the most influential institutions, authors, and research trends. Using keywords "digital forensic AND software," the data collection process involved filtering by date range, document type, and subject matter, resulting in 427 journal articles. The analysis highlights the most productive institutions, years, fields of study, active authors, and publishers. This data is valuable for researchers and practitioners in digital forensics, particularly those interested in software applications, providing insights into the most significant contributions and aiding future research development. Highlights: Research in the field of digital forensics is growing rapidly, with the Université de Lausanne being the leading institution in the number of publications. Computer science is the most popular field of study in digital forensics, with a focus on analysing software and file systems. Elsevier B.V. is the leading publisher in digital forensics, with the journal Digital Investigation as the main source of publications.